Analisis Penggunaan Bahan Bakar Liquified Petroleum Gas (LPG) Terhadap Torsi dan Daya Pada Supra X 125R Tahun 2010 - Setiawan, Mochamad Fansyah Ari; Triono, Bambang (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The objectives of this research are: (1) Analyzing the use of LPG fuel on torque and power on the 2010 Supra X 125R motorbike. (2) Investigating the torque and power on the 2010 Supra This research was conducted at RAT MOTOR SPORT BENGKEL. The population in this study was the 2010 Supra X 125R motorbike and the sample in this research was the 2010 Supra Based on the research results, it can be concluded: (1) The use of LPG fuel on the 2010 Supra X125R motorbike cannot be applied directly, because the Supra Changes must be made to the carburetor, namely by changing the size of the pilotjet to #118 and the mainjet to #200 because the AFR stoichiometry of LPG is 21: 1. (2) The use of LPG fuel does not increase the maximum torque on the wheel axle. Maximum torque when using pertalite fuel occurs at engine speed of 4459 rpm, which is 8.62 N*M. Meanwhile, the maximum torque when using LPG fuel occurs at engine speed of 4328 rpm, which is 8.19 N*M or 0.43 N*M lower than the torque when using pertalite fuel. (3) The use of LPG fuel does not increase the maximum power on the wheel axle. Maximum shaft power when using pertalite fuel occurs at engine speed of 5846 rpm, which is 6.23 HP. Maximum shaft power when using LPG fuel occurs at engine speed of 5464 rpm, which is 5.83 HP or 0.4 HP lower than the power when using pertalite fuel. (4) The decrease in top end when using LPG fuel is because LPG fuel has a faster flame propagation than gasoline, so that LPG will burn before the piston reaches 10º TDC or in other words the ignition timing on gasoline motorbikes is not correct when using LPG fuel. (5) The decrease in motor performance when using LPG fuel is caused by differences in the ignition characteristics of the fuel, so to increase the performance of the motor when using LPG fuel is to adjust the ignition to be more precise.